ANALISIS STRATEGI PADA UMKM SEPATU KOTAMA DENGAN PORTER'S FIVE FORCES - Gultom, Muhammad Reza Firdaus; Lumbanraja, Posma (Talenta Publisher, 2022)
Micro, small and medium enterprises (MSMEs) are growing so fast in Indonesia. The government's encouragement of the growth of MSMEs has been one of the factors in people to change their mindset from looking for work to open employment. In 2017 there were 527,053 MSME units registered in Medan City. With a sufficient number of MSMEs, this will certainly help the Indonesian economy in increasing the country's GDP. However, these MSMEs need to have the right strategy to be able to compete with other MSMEs as well as large enterprises In this study, an analysis was conducted a qualitative analysis to determine the competitive strategies of the MSMEs in the footwear industry in Kotama Medan. Data analysis was conducted using Porter's 5 Forces analysis technique, reduction of data, presentation of data and drawing conclusions from the results of the data. Based on the analysis 5 Forces Porter's analysis, it can be concluded that Kotama's MSME has adopted 3 competitive strategies suggested by strategies suggested by Porter, namely low cost strategy, product differentiation and focus on target segmentation.